Empirical studies of financial innovation: lots of talk, little action? - W. Scott Frame; Lawrence J. White (Federal Reserve Bank of Atlanta, 2002)
This paper reviews the extant empirical studies of financial innovation. Adopting broad criteria, the authors found just two dozen studies, over half of which (fourteen) had been conducted since 2000. Since some financial innovations are examined by more than one study, only fourteen distinct phenomena have been covered. Especially striking is the fact that only two studies are directed at the hypotheses advanced in many broad descriptive articles concerning the environmental conditions (e.g., regulation, taxes, unstable macroeconomic conditions, and ripe technologies) spurring financial innovation. The authors offer some tentative conjectures as to why empirical studies of financial innovation are comparatively rare. Among their suggested culprits is an absence of accessible data. The authors urge financial regulators to undertake more surveys of financial innovation and to make the survey data more available to researchers.
Keywords: 330; Financial modernization; Banks and banking; Patents; Securities